Strategi Mitigasi Risiko pada Proyek Pengadaan Kereta Luxury di PT. X dengan Pendekatan House of Risk (HOR) - Ni Luh Made Pretty Wulansari; Sinta Dewi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
PT INKA Multi Solusi is a company that focuses on providing manufacturing services for railway and land transportation products. In its business process PT. X uses the Make To Order (MTO) production system. In carrying out the project, it is not uncommon for delays in the arrival of materials, especially in the procurement project of 10 luxury train cars. This study aims to identify risks for cause and impact analysis and then developed to carry out effective risk mitigation planning used for risk control, and continuous monitoring of control. To solve this problem, the author uses the House of Risk (HOR) approach to be able to determine risk agents who must be prioritized first to then choose the most effective action to reduce the potential risks posed by risk agents. Based on the results of data processing, 11 dominant risk agents were obtained which must be solved with effectiveness to difficulity sequentially of 28141.73, 22919.03, 21032.7125, 20944.31, 20679.75, 16333.17, 16137.35, 15861.75, 9590.543, 7066.475, and 5975.095.